Detection of subclinical vitamin K deficiency in neurosurgery with PIVKA-II. (19th May 2017) - Dahlberg, Sofia; Nilsson, Caroline Ulfsdotter; Kander, Thomas; Schött, Ulf
Abstract: Vitamin K is known for supporting the carboxylation of hepatic coagulation proteins. Levels of proteins induced by vitamin K absence for factor II (PIVKA-II) reflect hypocarboxylated prothrombin and can be used to detect subclinical vitamin K deficiency. The aim of this study was to determine the prevalence of perioperative subclinical vitamin K deficiency among neurosurgical patients using PIVKA-II and investigate the existence of any correlation to standard coagulation assays. Also, the antitumor effects of vitamin K were reviewed. Thirty-five patients undergoing brain tumor resection were included. Blood samples were drawn preoperatively, at the end of surgery and in the morning after surgery. In addition to PIVKA-II, factor II and the Owren and Quick prothrombin times were analyzed. Seventeen of 35 patients had elevated PIVKA-II levels before surgery, which continued to be above normal range postoperatively. Median PIVKA-II and Owren prothrombin time (PT-INR) were increased on the morning day 1 postoperatively compared to before surgery, whereas Quick end-stage prothrombin time (EPT) decreased and factor II was unaffected. Postoperative complications were connected to high PIVKA-II increases. Positive correlations between PIVKA-II and factor II and body mass index (BMI) were found. In conclusion, PIVKA-II was increased in many patients preoperatively and then increased by the morning following surgery. Standard coagulation assays were largely non-pathological. Correlations were demonstrated between PIVKA-II and factor II and BMI. The effect of perioperative treatment with different vitamin K supplements should be investigated in future studies, as well as clinical trials evaluating their antitumor effects.